2017
DOI: 10.1063/1.4977956
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of bulk and surface polaritons in a magnetic-semiconductor superlattice influenced by a transverse magnetic field

Abstract: It is demonstrated that the effect of coexistence of bulk and surface polaritons within the same frequency band and wavevector space can be achieved in a magnetic-semiconductor superlattice providing a conscious choice of characteristic resonant frequencies and material fractions of the structure's underlying components as well as geometry of the external static magnetic field. The study is based on the effective medium theory which is involved to calculate dispersion characteristics of the long-wavelength ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…It is obvious that combining gyroelectric and gyromagnetic materials into a single gyroelectromagnetic system can bring many unique dispersion features, which are unattainable in separate subsystems. [36][37][38][39][40][41][42][43] In particular, in the present paper, we demonstrate that in a biaxial gyrotropic medium composed of magnetized ferrite and semiconductor layers, some specific distortions of isofrequency surfaces may occur. These distortions manifest themselves near the frequency of ferromagnetic resonance, where the magnetic subsystem possesses the properties of natural hyperbolic dispersion.…”
Section: Introductionsupporting
confidence: 58%
“…It is obvious that combining gyroelectric and gyromagnetic materials into a single gyroelectromagnetic system can bring many unique dispersion features, which are unattainable in separate subsystems. [36][37][38][39][40][41][42][43] In particular, in the present paper, we demonstrate that in a biaxial gyrotropic medium composed of magnetized ferrite and semiconductor layers, some specific distortions of isofrequency surfaces may occur. These distortions manifest themselves near the frequency of ferromagnetic resonance, where the magnetic subsystem possesses the properties of natural hyperbolic dispersion.…”
Section: Introductionsupporting
confidence: 58%
“…the structure is a finelystratified one. With taking into account the long-wavelength limit and involving averaging (homogenization) procedures from the effective medium theory (is not presented here; for details, see, [20,21,22,23]), the superlattice is further described by two tensors of relative effective permittivity and relative effective permeability written in the form:…”
Section: Superlattice Description and Dispersion Relationsmentioning
confidence: 99%
“…In our previous publications [19,20,21] it is demonstrated that the dispersion features of both bulk and surface polaritons that propagate through a magnetic-semiconductor superlattice can be rather complicated. Generally, it is found out that in such a structure being under an action of the external static magnetic field the bulk polaritons appear as ordinary and extraordinary elliptically polarized waves with very different characteristics, whereas the surface polaritons are of hybrid type that can possess branches of anomalous dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the fact that hyperbolicity requires plasma behavior in a certain direction of wavevector space and insulating behavior in the others leads to an option instead of metals along with dielectrics use some combination of semiconductors and magnetic materials (e.g., ferrites) as building blocks of the hyperbolic metamaterials [19]. This possibility becomes even more attractive considering that influence of an external magnetic field to such magneto-active structures allows to gain a control over waves dispersion features [20][21][22], nonreciprocal effect [23,24], and on their topological transitions [25,26]. Such systems are important for a number of practical applications in integrated photonic devices for telecommunications (see, for instance, [27] and references therein).…”
mentioning
confidence: 99%